Arthroscopic rotator cuff repair with or without PrP: our experience - Di Benedetto, Paolo; Di Benedetto, Enrico Daniele; Beltrame, Alessandro; Gisonni, Renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: Arthroscopical rotator cuff repair has good results, but the rate of tendon healing is 80% in small tears with a decrease to 30% in large and massive tears. Platelets are an endogenous source of growth factors present during rotator cuff healing. Aim of the work is checking if Cascade Autologous Platelet System may improve rotator cuff healing in small sovraspinatus tears. Methods: Each patient enrolled in cases  has surgical arthroscopical repair of sovraspinatus  small tear and then treated with intraoperatory Cascade. Patients of control group undergoing the same surgery with traditional arthroscopic repair. Follow-up time was at 3, 6, 12 month from surgery with evaluation of ROM, strength, Constant score, NRS. RMN was repeated at 12 month from surgery with evaluation of sovraspinatus tendon thickness, signal intensity, fat degeneration and muscle atrophy. Results: Between 2010 and 2013, 18 patients have undergone sovraspinatus repair in arthroscopic surgery  with intraoperatory Cascade and 18 patients with traditional arthroscopic repair. Only sovraspinatus tendon thickness and  signal intensity were  statistically difference in the cases group. In ROM, strength, Constant score, NRS, fat degeneration and muscle atrophy were not a statistically difference compared with controls. Conclusions: In small sovrapinsatus tears Cascade Autologous Platelet System did not result in improved ROM, strength, Constant score, NRS, tendon fat degeneration and muscle atrophy. Only sovraspinatus  tendon thickness and  signal intensity were improved.